Sosialisasi Perizinan Usaha Untuk UMKM pada Kelompok PKK Kelurahan Telaga Sari - M Miswaty; Muhammad Aghnie Ramdhani; Widya Ngudi Prahasto; Sabian Mauludian; Bima Yusril Musaputra; Sardi Sanjaya; Indri Septianing Ratri; R Rahmawati; Amalia Rahayu; Umar Bunga Wirayuda Busari; Raisha Ardyana (Community Service Journal (CSJ), 2024)
Socialization activities on business licensing were conducted on the PKK group of RT. 45 Telaga Sari Village in Balikpapan city. Licensing socialization was carried out considering the smoothness of a business for orderliness in complying with the regulations that apply in a region. Micro and Small Enterprises (MSEs) are a business sector that has an important role in the Indonesian economy. However, many still do not have a business license, either offline or online. Whereas, a business license can provide various benefits for MSEs, such as legal certainty, ease of access to capital, tax facilities, and government assistance. Therefore, this article aims to inform the procedures, benefits, and obstacles in making a micro and small business license (MSBL). This article uses a qualitative descriptive method by collecting data from various sources, such as the OSS website, Kompas.com, OCBC NISP, and Yukk.co.id. The analysis results show that the procedure for making MSBL offline includes filling out forms and documents of requirements at the sub-district office, while online includes registering on the OSS website and filling in business data. The benefits of having MSBL include obtaining business legality, legal protection, ease of capital, tax facilities, and government assistance. The obstacles faced by MSEs in making MSBL include lack of awareness, knowledge, and ability to manage licensing, as well as bureaucracy and complicated requirements. This article recommends that MSEs be more proactive and initiative in making MSBL, as well as utilizing the online services provided by the government. The government also needs to increase socialization, education, and facilitation related to licensing, as well as simplify the processes and requirements needed. Thus, it is expected that the number of MSEs that have business licenses can increase, so that they can contribute more optimally to the national economy. Keywords: MSEs licensing, Micro and Small Business License (MSBL), Online Single Submission (OSS), Benefits and obstacles, Recommendations